Quantum friction in two-dimensional topological materials - Farias, María Belén (2018)
We develop the theory of quantum friction in two-dimensional topological materials. The quantum drag force on a metallic nanoparticle moving above such systems is sensitive to the nontrivial topology of their electronic phases, shows a novel distance scaling law, and can be manipulated through doping or via the application of external fields. We use the developed framework to investigate quantum friction due to the quantum Hall effect in magnetic field biased graphene, and to topological phase transitions in the graphene family materials. It is shown that topologically nontrivial states in two-dimensional materials enable an increase of two orders of magnitude in the quantum drag force with respect to conventional neutral graphene systems.